2021
DOI: 10.31234/osf.io/x6nbf
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gaze-dependent evidence accumulation predicts multi-alternative risky choice behaviour

Abstract: Choices are influenced by gaze allocation during deliberation, so that fixating an alternative longer leads to increased probability of choosing it. Gaze-dependent evidence accumulation provides a parsimonious account of choices, response times and gaze-behaviour in many simple decision scenarios. Here, we test whether this framework can also predict more complex context-dependent patterns of choice in a three-alternative risky choice task, where choices and eye movements were subject to attraction and comprom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 49 publications
(93 reference statements)
1
7
0
Order By: Relevance
“…They found that decoys result in more consecutive shifts of attention between the decoy and target, suggesting an increase in comparing target and decoy options during choice. Molter et al (2021) found that target options received greater relative dwell time than competitor options in both the attraction and compromise effects. Overall, these results show that attention and how it shifts during deliberation plays a key role in understanding context effects.…”
Section: Empirical Studies Of Attention and Context Effectsmentioning
confidence: 96%
See 2 more Smart Citations
“…They found that decoys result in more consecutive shifts of attention between the decoy and target, suggesting an increase in comparing target and decoy options during choice. Molter et al (2021) found that target options received greater relative dwell time than competitor options in both the attraction and compromise effects. Overall, these results show that attention and how it shifts during deliberation plays a key role in understanding context effects.…”
Section: Empirical Studies Of Attention and Context Effectsmentioning
confidence: 96%
“…Some of these models, such as Multi-alternative Decision Field Theory (MDFT; Roe, Busemeyer, & Townsend, 2001), have been studied and tested extensively over the years. Other models, such as the Normalization and Urgency Model (Tajima, Drugowitsch, Patel, & Pouget, 2019) and the Gaze-dependent Leaky Accumulator (GLA; Molter, Thomas, Huettel, Heekeren, & Mohr, 2021) are relatively new theories and thus have been studied less. Looking at Table 1, one might wonder which model is the "best".…”
Section: Dynamic Models Of Context Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that decoys result in more consecutive shifts of attention between the decoy and target, suggesting an increase in comparing target and decoy options during choice. Molter et al (2021) found that target options received greater relative dwell time than competitor options in both the attraction and compromise effects.…”
Section: Empirical Studies Of Attention and Context Effectsmentioning
confidence: 96%
“…It does not however attempt to understand the process responsible for the allocation of attention. Recently, gaze-dependent evidence accumulation models have also been leveraged to study context effects in multi-alternative, multi-attribute choice (Molter et al, 2022). However, because attention is treated as an exogenous variable in the aDDM and other gaze-dependent models, the models make no predictions for the effect that different spatial layouts, for example, will have on attention and (consequently) decision making.…”
Section: Relationships To Other Modeling Approachesmentioning
confidence: 99%